CHILDCARE FACILITIES AT USM ISLAMIC CENTRE FOR MOTHERS GOING FOR TARAWIH PRAYERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 23 June 2015 The Islamic Centre of Universiti Sains Malaysia (USM) has made available facilities to mothers with young children who wish to go for the nonobligatory Tarawih prayers.